Sarcomeric gene mutations in phenotypic positive hypertrophic cardiomyopathic patients in Indian population - Ahmad, Syed Abrar; Chavan, Chandrakant; Badani, Rajesh; Wankhade, Varsha (Cellular and Molecular Biology, 2022)
HCM is a monogenic cardiac disorder with a high risk of sudden cardiac death, heterogeneous phenotypic expression and genetic profile. HCM is expressed as autosomal dominant in fashion with the prevalence of 1:500 in the general population. The main objective of the current study was to unravel the mutation status in sarcomeric genes in urbanizing Pune population. HCM patients were recruited from Bharti hospital and Poona hospital and research centre, Pune after being screened by 2-D echocardiography. DNA was extracted from whole blood samples and PCR amplification was performed for selected exons from pre-selected genes, amplimers of >300 b.p were restriction digested and the SSCP technique was optimized for maximum result output. HCM patients shows the maximum prevalence of mitral regurgitation (23.3%) while the minimum prevalence was left auricular diameter (10%). Maximum variation spectrum was present in MYBPC3 genes as most of them were “benign” type as per Polyphen-2 tool status. Mutations in the MYH7 gene produce a prominent impact on splicing by the creation of a new SRP40 binding site (Exon Splicing Enhancer) as predicted by Human Splicing Finder 3.1. I736T mutation in the MYH7 gene results in replacement of β-strand by α-helix upstream from mutation site which may have a profound impact on protein tertiary structure as predicted by Polyphen-2 tool (probably damaging-1.00). Also, two ‘novel’ mutations and one ‘novel’ variation were reported in the present study. Thus, the MYBPC3 gene shows maximum mutation load among other sarcomeric genes. Double gene mutations do not represent much severe pathophysiology as compared to single gene mutated and genotypic negative HCM patients.